Development of Bearing Capacity Factor in Clay Soil with Normalized Undrained Shear Strength Behavior using The Finite Element Method - Lim, Aswin (Institut Teknologi Bandung, 2011)
Abstract. This paper presents a development of bearing capacity factor chart for strip footing laying on clay soil with normalized undrained shear strength using finite element method. Since stress history and normalized soil engineering properties concept were introduced in 1974 by Ladd and Foot, the new approach of design for clays has evolved. In order to accommodate this new approach, a study is conducted to see the effect of the normalized soil properties on bearing capacity factor, especially footings on clays. The results show that the effect of normalized undrained shear strength is more sensitive for soft clays rather than stiff clays. Abstrak. Makalah ini menyajikan pengembangan grafik faktor daya dukung untuk pondasi lajur pada tanah lempung dengan normalisasi kuat geser tak terdrainase tanah menggunakan metode elemen hingga. Sejak konsep historik tegangan dan normalisasi properti teknik tanah yang diperkenalkan pada tahun 1974 oleh Ladd dan Foot, pendekatan baru untuk perencanaan untuk tanah lempung telah berevolusi. Untuk mengakomodasi pendekatan baru ini, sebuah studi dilakukan untuk mempelajari efek dari normalisasi properti tanah pada faktor daya dukung, khususnya pondasi pada tanah lempung. Hasil studi menunjukkan bahwa efek normalisasi kuat geser tak terdrainase lebih sensitif terhadap lempung lunak dibandingkan lempung teguh.